Pengaruh Model Pembelajaran Mind Mapping Berbantuan Powerpoint Terhadap Hasil Belajar Pada Materi Lingkaran Kelas VIII - Wahida, Shofia; Nanang Nabhar Fakhri Auliya (Cartesian: Jurnal Pendidikan Matematika, 2024)
This research aims to prove whether or not there is an influence of the Mind Mapping Type Cooperative Learning Model Assisted by Powerpoint on the Mathematics Learning Outcomes of Class VIII Students on Circle Concept Material. This research uses a quantitative approach with an experimental type of research. Meanwhile, the design applied is a true experimental design in the form of a posttest only control design. The data collection method in this research used a multiple choice test with 10 questions. Collecting the data obtained, the results of the calculations obtained an average value for the experimental class of 69, while the average value for the control class was 51. Based on the results of hypothesis testing using SPSS, the results obtained were a value of  = 1,670. So, is rejected or  is accepted. This research resulted that the mathematics learning outcomes of students who were subjected to the mind mapping learning model in the experimental class were better than the mathematics learning outcomes of students in the control class who were subjected to the direct learning model.